2017
DOI: 10.1111/imm.12720
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of different interleukin‐17‐producing T‐cell subsets is associated with liver fibrosis in chronic hepatitis C

Abstract: Studies have suggested the pivotal role of T helper type 1 (Th1) -related cytokines on the outcome of hepatitis C virus (HCV) infection. Nevertheless, the role of different interleukin-17 (IL-17) -secreting T cells on chronic hepatitis C (CHC) is less clear. Here, the in vivo IL-1β, IL-6, and IL-17 levels were positively correlated with both alanine transaminase (ALT) levels and hepatic lesions. When compared with the control group, CHC patients showed a lower proportion of IL-17-secreting (CD4 and CD8 ) T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…In vivo levels of IL-6 have been associated with plasma ALT levels and the degree of liver fibrosis in patients with HCC in HCV monoinfected patients [ 71 ] and a previous study demonstrated a low detection rate of IL-6 in patients infected with OBI when compared to healthy individuals and patients who resolved HBV infection [ 62 ]. We found high levels of IL-6 in the OBI/HCV group in our study and significant difference between OBI/HCV compared to monoinfected HBV group and healthy controls, this increase in IL-6 expression could be attributed to HCV co-infection, since several studies have already found that this cytokine is associated with HCV chronic infection [ 63 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo levels of IL-6 have been associated with plasma ALT levels and the degree of liver fibrosis in patients with HCC in HCV monoinfected patients [ 71 ] and a previous study demonstrated a low detection rate of IL-6 in patients infected with OBI when compared to healthy individuals and patients who resolved HBV infection [ 62 ]. We found high levels of IL-6 in the OBI/HCV group in our study and significant difference between OBI/HCV compared to monoinfected HBV group and healthy controls, this increase in IL-6 expression could be attributed to HCV co-infection, since several studies have already found that this cytokine is associated with HCV chronic infection [ 63 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo levels of IL-6 have been associated with plasma ALT levels and the degree of liver brosis in patients with HCC in HCV monoinfected patients [71] and a previous study demonstrated a low detection rate of IL-6 in patients infected with OBI when compared to healthy individuals and patients who resolved HBV infection [62]. We found high levels of IL-6 in the OBI/HCV group in our study and signi cant difference between OBI/HCV compared to monoinfected HBV group and healthy controls, this increase in IL-6 expression could be attributed to HCV co-infection, since several studies have already found that this cytokine is associated with HCV chronic infection [63,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo levels of IL-6 have been associated with plasma ALT levels and the degree of liver brosis in patients with HCC in HCV monoinfected patients [51]. We found high levels of IL-6 in the occult group and it is well known that IL-6 can play two important roles in the pathogenesis of hepatitis B, can protect the liver from virus infections by stimulating immune responses against infected hepatocytes and can inhibit the HBV entry in hepatocytes up to 90% when cells are treated with IL-6 resulting in a marked reduction in cccDNA and HBsAg secretion [52].…”
Section: Discussionmentioning
confidence: 99%